2022
DOI: 10.1186/s12887-022-03372-5
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of brain injury in preterm infants with sepsis - associated encephalopathy

Abstract: Sepsis-associated encephalopathy (SAE) is characterized by brain dysfunction during sepsis, without central nervous system infection. Here, we explored the molecular basis of brain injury in preterm infants with SAE. From Jan 2016 to Dec 2019, a total of 20 preterm infants were hospitalized in the neonatal intensive care unit (NICU) of our hospital, including 10 preterm infants with SAE (SAE group) and 10 preterm infants without encephalopathy after sepsis (no SAE group). Among the 20 premature infants, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…A clinical study conducted on peripheral blood samples collected from 20 premature infants revealed a potential correlation between high expression of miRNA-1197 and low expression of miRNA-485-5p with the pathogenesis of oxidative respiratory chain and energy metabolism in premature infants with SAE. These findings suggest a possible association with mitochondrial dysfunction during SAE (Gong et al, 2022). Common neuroinflammation often affects mitochondrial health in SAE.…”
Section: Organelle Dysfunctionmentioning
confidence: 69%
“…A clinical study conducted on peripheral blood samples collected from 20 premature infants revealed a potential correlation between high expression of miRNA-1197 and low expression of miRNA-485-5p with the pathogenesis of oxidative respiratory chain and energy metabolism in premature infants with SAE. These findings suggest a possible association with mitochondrial dysfunction during SAE (Gong et al, 2022). Common neuroinflammation often affects mitochondrial health in SAE.…”
Section: Organelle Dysfunctionmentioning
confidence: 69%
“…Критерії діагнозу сепсису: клінічні прояви; виявлення патогенних бактерій та/або умовно-патогенної флори, культивованих із крові та асептичних зразків тіла, катетера; два або більше позитивних результатів неспецифічних тестів на маркери запалення, наприклад, вміст лейкоцитів у периферичній крові >11,0 Г/л, лейкоцитарний індекс >0,2, підвищений вміст гострого С-реактивного білка (+ якісно, або >5 ммоль/л кількісно) [6].…”
Section: матеріали та методи дослідженняunclassified
“…Preliminary evidence has indicated that urine extra cellular vesicles derived miRNAs can be used as biomarkers for necrotizing enterocolitis in premature infants (36). Moreover, many studies have investigated the application of exosomal miRNAs as biomarkers or therapies in the treatment of preterm infants (37)(38)(39)(40). Multiple studies have reported changes in compositions and miRNAs within the body through diet or dietary regulation.…”
Section: Introductionmentioning
confidence: 99%